Use of farm power as water: farm management - Sunderam, M. (My University, 1981)
'.i.'bi,:; 4is~a~1Oft 1. S't&1omi ttted a. a partial ful:i:ilment in requi&'ement. fOZ' t:be ".$0 c::cw:se . in .L'1vironmental eclence. to tbe NaturalScience Faculty- Uni~.1ty of Colombo. 'l'he '3&111pw;:poee of cboo8iDg t:biCl ~1cu1ar SW;jjecM is dUe to the. fact:. that. UJ:';eat. need for c1evelOp1Defttand -g8II8Dt of watc neourc:e. in sri Lanka. To 1DOet.the bIuIic neceae1t.y of t:be growing population ~ fO1: more prodcot:1on which relies on more _~.r aad land. Thougb history baa recorded -y nt"n." of 1nipt.J.on pro ject.a , Bel: auffic1encyia yet an unceacbed target:. one of ube eontZ'!buteJ:y cow:eed fOJ: tM. is poor water ~ OJ: lack of water managemeat.. A proper _tat: manageme.nt. ahO\1l4 .bave a mutual relationabl.p 1»t.ween t:be fumleve1 8ftd bigb l.evel manayC/:lent..30, 1t. 18 cJ.eazrthat. vat_, as well.. the other .t...'1p11t8used in a fam .. very J.mpor:1:.ant. which should bemanagec! well in or&R: to achieve hi\.jh product.ion rates. In t h 1s repoI1:. 1t 18 d1acuued tbe ~ of farm pOWer U88 in a vat- managemeat. .cnome vbicb helps to {Jive a ijood reault likethe otherinput.. j?or caa&-studie. ":~la It ,pro:lect. u-ea in the dry zone vaG cbosen, ample inf0l:t3ation about the area was ~at bered and aJ.so oll88rVatioDa were made where eve7: neceseuy end possible. Fresh data about the usage of farm power at. KanduUa vas collected. With'thi8 aa a backgJ:ound the . problems are 4i.ecussed and solutions suggest.ed. The first. part. of the report. 1s tbe 11terature review of the water managemen't object.1 we as carried out;. in t:.be inigaUon project.s of the dry acme. Since Ithe patt.ern of managemen.t.is a.tmila2:'in ..u aebGmesthe problema are quite identical"ao, a general view ia d1acribed quoting acme sp8Cialearamp1e8. An appendix is attached behind. containing tbe relevant. tables and graphs in order to illuaUate the review further. Tbe main report. of the study area and the discus.ion follows t'O18. %t is further enr lobed by mapa and tables.